Elucidation of the nucleotide sequence of chicken calcitonin mRNA: direct evidence for the expression of a lower vertebrate calcitonin-like gene in man and rat. - Lasmoles, F (1985)
Calcitonin shows considerable divergence in amino acid sequence between lower vertebrates and higher vertebrates. Immunoreactive salmon-like calcitonin molecules are present in the thyroid of man and rat. Elucidation of the almost complete sequence of chicken calcitonin mRNA revealed that the calcitonin precursor in chickens had the same organisation as in higher vertebrates (man and rat) but showed considerable differences in amino acid sequence. cDNA probes specific for chicken calcitonin mRNA hybridized to poly(A)-rich RNA extracted from a case of medullary carcinoma of the thyroid and from murine thyroid. These results suggest the expression in man and rat of a gene coding for an avian calcitonin-like precursor.